2007
DOI: 10.1136/jech.2006.055426
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis-specific sick leave as a risk marker for disability pension in a Swedish population

Abstract: Objective: To investigate diagnosis-specific sick leave as a risk marker for subsequent disability pension. Design: A prospective population based cohort study. Exposure to a new medically certified sick leave episode of more than seven days by diagnosis during 1985 was examined in relation to incident causespecific disability pension through 1996. Participants: The total non-retired population of one Swedish county aged 16 to 49 years, alive and not in receipt of a disability pension at the end of 1985 (176 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 24 publications
6
65
0
3
Order By: Relevance
“…It indicates, by definition, temporary work disability due to the illness of an employee. In addition to temporary illness, chronic diseases and poor perceived health are reflected in higher absence rates (1)(2)(3)(4), and high long-term absence predicts permanent work disability and death (5)(6)(7). Earlier studies also show that past absence is an independent predictor of future absence (8).…”
mentioning
confidence: 79%
“…It indicates, by definition, temporary work disability due to the illness of an employee. In addition to temporary illness, chronic diseases and poor perceived health are reflected in higher absence rates (1)(2)(3)(4), and high long-term absence predicts permanent work disability and death (5)(6)(7). Earlier studies also show that past absence is an independent predictor of future absence (8).…”
mentioning
confidence: 79%
“…However, Månsson et al also studied middle-aged men, but used a reference group similar to ours (not including underweight), which may explain why the results were consistent with our findings but not with those of Rissanen et al 13 The association of obesity status at age 17-20 years with later DP due to psychiatric disorders other than nonaffective disorders (including schizophrenia) may partially be mediated by psychosocial stress due to negative attitudes toward individuals deviating from the predominant norms and BMI, psychiatric disorders and disability pension M Kark et al values in society about body size and shape. 11,[18][19][20] The less acceptable it is to be underweight, overweight or obese in a society or group, the stronger the psychological pressure may become. The perception of being too heavy according to prevailing body appearance norms may create considerable psychosocial stress and lower self-esteem, and unsuccessful attempts to lose weight may worsen the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Employed people with mental disorders lose three times more work days in a 12-months' period compared to people without mental disorders [2]. Furthermore, mental disorders are associated with an increased risk of disability pensioning [5][6][7][8][9]. The Organization for Economic Co-operation and Development reported that mental disorders account for up to one-third of disability pension awards in western European countries [10].…”
Section: Introductionmentioning
confidence: 99%